Living Islam - "Ahmed, Akbar S." (London, 1993)
An examination of Islam, its history, culture and values. It discusses the conflict between Islam and Western ideologies, and the problems that Muslims face in the modern world. The pressures and practices of Muslims living as minorities in India, Israel, America and Britain are explored.
Keywords: Islam